2023
DOI: 10.3390/nano13142093
|View full text |Cite
|
Sign up to set email alerts
|

MOF-Derived Co Nanoparticles Catalyst Assisted by F- and N-Doped Carbon Quantum Dots for Oxygen Reduction

Abstract: The oxygen reduction reaction is crucial in the cathode of fuel cells and metal–air batteries. Consequently, designing robust and durable ORR catalysts is vital to developing metal–air batteries and fuel cells. Metal–organic frameworks feature an adjustable structure, a periodic porosity, and a large specific surface area, endowing their derivative materials with a unique structure. In this study, F and N co-doped on the carbon support surface (Co/FN-C) via the pyrolysis of ZIF-67 as a sacrificial template whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
0
0
Order By: Relevance
“…In recent years, significant interest of researchers has been devoted to green catalysis, energy conversion, and environmental remediation. The distinct characteristics of laserinduced MOF derivatives make them promising candidates for multifunctional materials in these fields, which has been proven by many reports [15][16][17][18][19]. However, the full potential of laser-assisted synthesis in exploring MOF-derived materials for electrochemical sensor applications has not been fully realized.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, significant interest of researchers has been devoted to green catalysis, energy conversion, and environmental remediation. The distinct characteristics of laserinduced MOF derivatives make them promising candidates for multifunctional materials in these fields, which has been proven by many reports [15][16][17][18][19]. However, the full potential of laser-assisted synthesis in exploring MOF-derived materials for electrochemical sensor applications has not been fully realized.…”
Section: Introductionmentioning
confidence: 99%
“…It is well confirmed that S-doping is beneficial for the production of electron-withdrawing/donating groups, such as SOx-C or/and C-S-C species on the carbon plane [7], thereby modulating the electronic state of adjacent carbon atoms [8]. Moreover, the introduction of extra active units into heteroatoms-doped carbon substrates, including metal oxides, phosphides, sulfides, etc., is favorable for the further improvement of catalytic performance owing to co-catalysis [9][10][11][12]. Nowadays, the most widely investigated ORR electrocatalysts are mainly focused on Fe and Co metallic compounds [13,14].…”
Section: Introductionmentioning
confidence: 99%